Proyecto de desarrollo comunitario de Cuniburo Cangahua a través de la IAP, para la producción del cuy - Neppas Riquelme, Andrea Carolina (2007)
This community development project of Cuniburo Cangahua, reflects the work that can be achieved with a community applying Participatory Action Research as a development tool for the work of organizations and social movements seeking community development and social transformation with in practice the participation of those involved.